To Understand How Digital Literacy Affect the Employability Among Graduates in Malaysian Job Market (Wire Insights: Journal of Innovation Insights, 2023)
The raising importance in the digital literacy had been providing the expectations on the impact of the digital literacy among the universities graduates against the employability of the graduates in the Malaysian job market. The previous study had suggested that the digital literacy remained as the significant driving factor that will contribute to the positive impact in increasing the employability among the graduates in the job market. With this, the research methodology had been developing the quantitative study to analyse the data input based on the 150 questionnaires to explore the relationship between the independent variable of digital literacy against the dependent variable of employability among graduates in the job market. The empirical evidence had observed the result suggesting the significant relationship between the independent variable of digital literacy against the dependent variable of employability among graduates in the job market. However, there is no indication of the positive correlation being presence between the two variables showed the disagreement based on the initial understanding drawn from the previous study. This had provided the significance contribution to the reference of future studies creating opportunities for the scope of study can be extended to potential exploration of new knowledge in the future research.